PENENTUAN TOTAL MIKROBA INDIKATOR, NITRAT, DAN FOSFAT PADA SUNGAI TAPUNG KIRI - Rosidah '; Yuli Haryani; Ganis Fia Kartika (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2014)
The aim of this study was to analyze physicochemical parameters  and  total  microbial indicators  of river water  in Tapung Kiri river. Water samples were taken from  4 sampling sites in  July  2013.  The results showed that the range of  TDS,  turbidity,  electrical conductivity,  and nitrate in  the  water samples  were  9-21 mg/L, 3.89-41.1 NTU, 17.72-42.0 µs/cm,  and  0.112-0.508 mg/L, respectively which  were  below of  the threshold value. Temperature, pH, DO,  and  phosphate content range  were  27-29oC,  4.75-6.30,  3.36-3.96 mg/L, and 0.089-0.235 mg/L at the threshold value based on PP No 82 2001. The level of Coliform  and  E. coli  contamination in  the  water samples were  0.4-18×10 3 CFU/mL and 0.1-4×10 3 CFU/mL.  The level of total bacteria contamination was found in all samples ranged from  0.43-4.6×10 4 MPN/mL, while the fungi  contamination was  0.1-0.3×10 3 CFU/mL.